Rebelwing - Tang, Andrea (Razorbill, 2021)
At New Columbia Preparatory Academy in a near-future Washington, D.C., black market smuggler Prudence Wu and friends Anabel, Alex, and Cat become key players in a conflict with the United Continental Confederacy.